Innovation potential scale (IPS): construction and validity evidence of a measure for the work context - Gustavo Henrique Silva de Souza; Nilton Cesar Lima; Fernanda Cristina Barbosa Pereira Queiroz; Rafael Farias Gonçalves; Jamerson Viegas Queiroz (Innovation & Management Review, 2025)
Purpose - This article aims to develop a measure that assesses and maps the behaviors and traits of an individual with potential for innovation in the work context. To do so, it gathers evidence of factor validity and internal consistency. Design/methodology/approach - In the work context, innovation is often linked with the idea of intrapreneurship. Some experts have pointed out that intrapreneurial activities are essential for promoting innovation. However, it is not just about the activities - the key is to create an environment that supports innovation, fostering a culture where new ideas can thrive. To achieve the objectives of this research, we conducted two studies. The first study involved the construction of the innovation potential scale (IPS). In a theoretical, empirical way, the second study involved the administration of the IPS and a sociodemographic questionnaire to a sample of 621 Brazilians from 25 different occupations. Findings - The results introduce a nine-item measure for the innovative behavior assessment, along with its validity and psychometric properties. Furthermore, the results suggest that innovation potential is a unidimensional construct. Moreover, the study highlights the role of intrapreneurship as an explanatory axiom. This concept helps to understand the entrepreneurial behavior of various professionals and managers within their work context. Practical implications - This study contribute with as instrument that serves as a new powerful tool for understanding of the mechanisms that lead to innovation in the work context and stimulate the innovative potential of professionals and organizations. Originality/value - This study helps fill gaps in the literature on self-report assessment of innovative behavior. The traits linked with the construct have a contingent nature and are only potential.
Keywords: 650; Innovation; Behavior; Psychometrics; Intrapreneurship